(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effectiveness of using the educational Klosemeyer model in the achievement of students of the Department of Art Education in the subject of art history and the development of their attitudes towards the subject), and the current research community consisted of third-grade students in the Department of Art Education - College of Fine Arts - University of Baghdad for the academic year (2012). - 2013) - the second semester, numbering (90) male and female students, and it was confined to a sample consisting of (32) male and female students, who were distributed into two experimental and control groups, each group included (16) male and female students, and the researcher rewarded between the two groups in the variables (previous experience, age time, and the direction of matter).